2014
DOI: 10.1557/opl.2014.389
|View full text |Cite
|
Sign up to set email alerts
|

Title: Inkjet-printed rectifying metal-insulator-semiconductor (MIS) diodes for flexible electronic applications

Abstract: Inkjet printing is a well-accepted deposition technology for functional materials in the area of printed electronics. It allows the precise deposition of patterned functional layers on both, rigid and flexible substrates. Furthermore, inkjet printing is considered as up-scalable technology towards industrial applications. Many electronic devices manufactured with inkjet printing have been reported in the recent years. Some of the evident examples are capacitors, resistors, organic thin film transistors and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…silver (bulk work function: 4.26 to 4.74 eV), copper (bulk work function: 4.53 to 4.98 eV), aluminium (bulk work function: 4.06 to 4.28 eV), poly (3,4 ethylenedioxythiophene) poly (styrenesulfonate) (PEDOT:PSS, bulk work function: 5.1 eV) [20,21]. Either one of these functional conductive materials look simple to process, but in most of the cases it is challenging to appoint and locate them (having different work functions) adjacent to the semiconductor interface layer [22]. Recently, it has been reported that MIS structures show a rectifying behaviour [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…silver (bulk work function: 4.26 to 4.74 eV), copper (bulk work function: 4.53 to 4.98 eV), aluminium (bulk work function: 4.06 to 4.28 eV), poly (3,4 ethylenedioxythiophene) poly (styrenesulfonate) (PEDOT:PSS, bulk work function: 5.1 eV) [20,21]. Either one of these functional conductive materials look simple to process, but in most of the cases it is challenging to appoint and locate them (having different work functions) adjacent to the semiconductor interface layer [22]. Recently, it has been reported that MIS structures show a rectifying behaviour [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a thick insulating layer with 50 to 200 nm will block the charge carrier flow and will not show rectification [26]. However, if the insulator layer is leaky due to an irregular morphology produced by the mutual interaction/blend of the semiconductor to insulator interfaces it can lead to a voltage controlled leakage and to corresponding asymmetric current versus voltage curves [22]. Herein, we focus on assessing the electrical characteristics of MIS based diodes fabricated completely by inkjet printing technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation